Influence of thermal effect on upconversion luminescence of Y2(MoO4)3:Yb3+, Ln3+ (Ln = Er, Tm). (31st August 2018) - Pang, Tao; Peng, Wenbo
Abstract: Upconversion luminescence of Yb 3+ /Er 3+ and Yb 3+ /Tm 3+ co-doped Y2 (MoO4 )3 phosphors under 980 nm excitation is investigated. It is demonstrated that Yb 3+ co-doping causes a significant thermal effect. For Yb 3+ and Er 3+ co-doped case, the thermal effect, the long-distance energy migration and the energy transfer from Er 3+ to Yb 3+ are responsible for the abnormal luminescence quenching. In the case of Yb 3+ and Tm 3+ co-doped, the thermal effect improves the excited efficiency of Tm 3+, and thus the luminescence of Tm 3+ continues to strengthen at the Yb 3+ concentration that causes Er 3+ luminescence quenching. These results contribute to the design of the efficient upconversion materials.